Labour Hoarding and the Wage Share: Test of a Hypothesis - Marion, Gérard; Spencer, Byron (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1979)
The authors seek to build on the work of Bail and St. Cyr, Smith and Ireland, Solow, and others, in order to estimate the assessment of labour hoarding and test the relationship between labour hoarding and the wage share.